PEMANFAATAN RADAR CUACA UNTUK MENGIDENTIFIKASI SEBARAN ABU VULKANIK GUNUNG MERAPI 3 MARET 2020 - Febriati, Eriska (Jurnal Widya Climago, 2022)
Remote sensing is most often used to reveal atmospheric conditions such as weather radar. One of the objects captured by the instrument is volcanic ash. On March 3, 2020, Mount Merapi erupted in Sleman Regency between Central Java and the Special Region of Yogyakarta, releasing volcanic ash. The distribution of volcanic ash is very dangerous to health and the safety of the aviation world. This study aims to identify the distribution of volcanic ash by utilizing weather radar products. The radar products used in this research are CMAX, VCUT, and CAPPI V. Based on the product analysis, it was found that the maximum reflectivity value obtained was 20 dBZ. The eruption height reached 11 km. The detected volcanic ash material is in the form of solid material, namely the types of fine ash and coarse ash. The direction of movement of volcanic ash based on radar imagery is moving towards the east.